A depropargylation-triggered spontaneous cyclization based fluorescent "turn-on" chemodosimeter for the detection of palladium ions and its application in live-cell imaging. Issue 10 (20th January 2016) - Chen, Yu; Zhang, Minmin; Han, Yifeng; Wei, Jie
Abstract : A novel depropargylation-triggered spontaneous cyclization reaction based fluorescent turn-on chemodosimeter for the detection of palladium ions has been rationally designed and developed. Abstract : A novel depropargylation-triggered spontaneous cyclization reaction based fluorescent turn-on chemodosimeter for the detection of palladium ions has been rationally designed and developed. Based on the specific reactivity of the palladium promoted hydrolysis reaction, the probe exhibited a high selectivity and sensitivity for palladium ions. Furthermore, the probe was successfully used for fluorescence imaging of Pd 2+ in living cells.